2019
DOI: 10.1002/pts.2424
|View full text |Cite
|
Sign up to set email alerts
|

Digital image correlation analysis of vertical strain for corrugated fiberboard box panel in compression

Abstract: This work was aimed at examining the overall contributions to displacement of panels of compressed boxes, such as panel compression strain and flap and crease displacements. 3D digital image correlation (DIC) was used to analyse motion of side panels of corrugated fiberboard regular slotted containers. The vertical displacement and the vertical component of strain of the panel face during box compression test were examined. Measuring displacements of the whole compressed box with DIC enables measurement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…8 and 9. Similar observations were reported by Kueh et al (2019). During stacking on a pallet, the packages placed at the bottom of the stack tend to experience the highest loads resulting in a significant out-of-plane deformation of the vertical walls before total collapse (Viguié et al, 2011).…”
Section: Evolution Of the Displacement Field During Compressionsupporting
confidence: 81%
See 2 more Smart Citations
“…8 and 9. Similar observations were reported by Kueh et al (2019). During stacking on a pallet, the packages placed at the bottom of the stack tend to experience the highest loads resulting in a significant out-of-plane deformation of the vertical walls before total collapse (Viguié et al, 2011).…”
Section: Evolution Of the Displacement Field During Compressionsupporting
confidence: 81%
“…From the curves, a low stiffness was observed at the initiation of compression which could be explained to be due to the unevenness of the flaps being levelled as the upper platen starts to compress the carton (Kueh et al, 2019). Following this point is a linear region with the highest slope which gradually decreases up until the maximum load and is related to local buckling on the package (Kueh et al, 2019). Next, a sharp decrease in the maximum load occurs as the package fails (Viguié et al, 2010).…”
Section: Package Compression Strength and Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…When the FE simulations did not account for any material or geometrical reductions of the creases, the response was quite similar to the physical experiments where the flaps were replaced by tape, that is, no horizontal creases, which can be seen in Figure 18. The distinguished difference in box stiffness with and without horizontal creases for paperboard is described elsewhere, 9 and the impact on vertical displacement of corrugated boxes due to creases is also previously established 24 …”
Section: Resultsmentioning
confidence: 86%
“…More recently, the capability of digital imaging to study the deformation of CFCs during compression loading has been revealed. Kueh et al [94] used 3D digital image correlation (DIC) to examine the contributions to the displacement of panels of compressed cartons. A majority of incidences of vertical displacement of cartons are due to the top and bottom flap crease folds compressing.…”
Section: Compression Strengthmentioning
confidence: 99%